Reconsidering treatment guidelines for acute myocardial infarction during the COVID-19 pandemic - Jing Gao; Peng-Ju Lu; Chang-Ping Li; Hui Wang; Ji-Xiang Wang; Nan Zhang; Xiao-Wei Li; Hai-Wang Zhao; Jing Dou; Miao-Na Bai; Yu-Tian Shi; Jia Zhao; et al. (BMC Cardiovascular Disorders, 2022)
Abstract Background COVID-19 affects healthcare resource allocation, which could lead to treatment delay and poor outcomes in patients with acute myocardial infarction (AMI). We assessed the impact of the COVID-19 pandemic on AMI outcomes. Methods We compared outcomes of patients admitted for acute ST-elevation MI (STEMI) and non-STEMI (NSTEMI) during a non-COVID-19 pandemic period (January–February 2019; Group 1, n = 254) and a COVID-19 pandemic period (January–February 2020; Group 2, n = 124). Results For STEMI patients, the median of first medical contact (FMC) time, door-to-balloon time, and total myocardial ischemia time were significantly longer in Group 2 patients (all p < 0.05). Primary percutaneous intervention was performed significantly more often in Group 1 patients than in Group 2 patients, whereas thrombolytic therapy was used significantly more often in Group 2 patients than in Group 1 patients (all p < 0.05). However, the rates of and all-cause 30-day mortality and major adverse cardiac event (MACE) were not significantly different in the two periods (all p > 0.05). For NSTEMI patients, Group 2 patients had a higher rate of conservative therapy, a lower rate of reperfusion therapy, and longer FMC times (all p < 0.05). All-cause 30-day mortality and MACE were only higher in NSTEMI patients during the COVID-19 pandemic period (p < 0.001). Conclusions COVID-19 pandemic causes treatment delay in AMI patients and potentially leads to poor clinical outcome in NSTEMI patients. Thrombolytic therapy should be initiated without delay for STEMI when coronary intervention is not readily available; for NSTEMI patients, outcomes of invasive reperfusion were better than medical treatment.